Five-Coordinate Zinc(II) Complex: Synthesis, Characterization, Molecular Structure, and Antibacterial Activities of Bis-[(E)-2- hydroxy-N - Zhi-Qiang, Liu; Ng, Yoke Mui; Tiong, Pei Jen; Ruwaida Asyikin, Abu Talip; Nornadia, Jasin; Yi, Vivien Mian Jong; Tay, Meng Guan (Hindawi Publishing Corporation, 2017)
The titled Zn(II) complex was synthesized by reacting the compound (E)-2-hydroxy-N